2020
DOI: 10.3389/fbioe.2020.00778
|View full text |Cite
|
Sign up to set email alerts
|

Hand Resting Tremor Assessment of Healthy and Patients With Parkinson’s Disease: An Exploratory Machine Learning Study

Abstract: Hand Tremor and Inertial Measures using few features led to similar decision of the algorithms. Moreover, performance increased significantly according to the number of features used, reaching a plateau around 136. Finally, the results of this study suggested that kNN was the best algorithm to classify hand resting tremor in patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
0
20
0
2
Order By: Relevance
“…Despite its widespread potential, the continuing success of flavor phenotyping depends upon an adequate supply of metabolomics data. An analysis of the test accuracies obtained from supervised machine learning algorithms showed that the machine learning phases significantly influenced the accuracies [ 67 ]. Our work included the evaluation of a range of statistical and machine learning models for the prediction of flavor quality based on metabolite information.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its widespread potential, the continuing success of flavor phenotyping depends upon an adequate supply of metabolomics data. An analysis of the test accuracies obtained from supervised machine learning algorithms showed that the machine learning phases significantly influenced the accuracies [ 67 ]. Our work included the evaluation of a range of statistical and machine learning models for the prediction of flavor quality based on metabolite information.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that most of the eHealth applications use the data obtained from the sensors such as accelerometer, gyroscopes, smart watch/smart phone/wearables, EEG/ECG/PPG etc. Accelerometer or tri-axial accelerometers, gyroscopes are used in more number of cases for the detection of the freezing of gait [28], bradykinesia [29], tremors [30] stroke [31] using machine learning algorithms, compared to other inertial sensors or gait sensors. Moreover, accelerometers can also be used for activity monitoring [32] when detecting the conditions of heart disease/diabetes.…”
Section: A Description Of Sensors Used In the Studiesmentioning
confidence: 99%
“…Different types of widely used classification methods namely baseline classifiers are useful to explore various kinds of records and analyze their performance. After outlier detection and removal from primary and ANOVA Ftest, CSFS, MIFS, and RFE datasets, several widely used classifiers including Gaussian Naive Bayes (GNB) [34], [35], Logistic Regression (LR) [14], [36], Random Forest (RF) [37], [38], Decision Tree (DT) [22], Extreme Gradient Boosting (XGB) [39], [11], Gradient Boosting (GB) [23], K-Nearest Neighbour (KNN) [40], AdaBoost [41], Support Vector Machine (SVM) [21], Multi-layer Perceptron (MLP) [42], and Extra Trees (ET) [43] are used to investigate PD detection dataset more precisely.…”
Section: E Applying Baseline Classifiersmentioning
confidence: 99%